Study on Runoff and Infiltration for Expansive Soil Slopes in Simulated Rainfall - Wenkai Lei (Water, 2020)
In order to understand the hydrological process of expansive soil slopes, simulated rainfall experiments were conducted to study the effects of slope gradient and initial soil moisture content on runoff and infiltration for expansive soil slopes located in south China. The field program consisted of four neighboring slopes (70%, 47%, 32%, and 21%) instrumented by a runoff collection system and moisture content sensors (EC-5). Results from the monitored tests indicate that there was delay in the response of surface runoff. The runoff initiation time decreased with initial soil water content and increasing slope gradient. After the generation of runoff, the cumulative runoff per unit area and the runoff rate increased linearly and logarithmically with time, respectively. The greater the initial soil moisture content was, the smaller the influence of slope gradient on runoff. A rainfall may contribute from 39% to about 100% of its total rainfall as infiltration, indicating that infiltration remained an important component of the rainwater falling on the slope, despite the high initial soil water content. The larger the initial sealing degree of slope surface was the smaller the cumulative infiltration per unit area of the slope. However, the soil moisture reaction was more obvious. The influence of inclination is no longer discernible at high initial moisture levels. The greater the initial soil moisture content and the smaller the slope gradient, the weaker was the change of soil water content caused by simulated rainfall. The influence of initial soil moisture content and slope gradient on the processes of flow and changes of soil water content identified in this study may be helpful in the surface water control for expansive soil slopes.